Expansion of PmBEAT genes in the Prunus mume genome induces characteristic floral scent production. Issue 1 (1st February 2019) - Bao, Fei; Ding, Anqi; Zhang, Tengxun; Luo, Le; Wang, Jia; Cheng, Tangren; Zhang, Qixiang
Abstract: Prunus mume is the only plant in the genus Prunus of the Rosaceae family with a characteristic floral scent, and the main component of this scent is benzyl acetate. By contrast, benzyl acetate is not synthesized in Prunus persica flowers. Here, we searched for benzyl alcohol acetyltransferase ( BEAT ) genes based on genomic data from P. mume and P. persica and found 44 unique PmBEATs in P. mume . These genes, which were mainly detected in clusters on chromosomes, originated from gene duplication events during the species evolution of P. mume, and retroduplication and tandem duplication were the two dominant duplication patterns. The genes PmBEAT34, PmBEAT36 and PmBEAT37, which were generated by tandem duplication, were highly expressed in flowers, and their highest levels were detected during the blooming stage. In vitro, PmBEAT34, PmBEAT3, and PmBEAT37 all had benzyl alcohol acetyltransferase activity that was localized in the cytoplasm. Overexpression of the PmBEAT36 or PmBEAT37 genes increased benzyl acetate production in the petal protoplasts of P. mume, and interference in the expression of these genes slightly decreased the benzyl acetate content. In addition, light and temperature regulated the expression of the PmBEAT34, PmBEAT36 and PmBEAT37 genes. According to these results, we hypothesize that the expansion of the PmBEAT genes in the genome induce the characteristic floral scent of P. mume . Chinese plum: Unraveling the genetics of scent: Prunus mume, Chinese plum, owes its unique scent to extra gene copies. Researchers knew the main component of P. mume blooms' prized scent, but the details of its production were unknown. Qixiang Zhang at the Beijing Forestry University and co-workers investigated the genetic basis of the scent, and uncovered an interesting evolutionary tale. A search for the scent production genes showed that P. mume has 44 copies; closely related P. persica, which lacks the special scent, has only two. Further analysis showed that the genes are clustered together, indicating they originated from duplication events, the evolutionary equivalent of accidental copying. The superfluous copies, released from their usual responsibilities, were free to evolve new functions, including scent production. These results illuminate how new plant traits can evolve, and unravel the mystery of this special scent.